PEDAGOGICAL CONDITIONS FOR FORMING ETHNO-PEDAGOGICAL COMPETENCE OF FUTURE TEACHERS IN THE REPUBLIC OF MOLDOVA - Tatiana PANCO (Acta et Commentationes, Sciences of Education, 2020)
The article discusses the pedagogical conditions that contribute to the successful formation of the ethno-pedagogical competence. The author suggests using the task approach in the process of forming the future teachers’ ethno-pedagogical competence. The proposed technology of using the tasks ensures the efficient formation of the described components of the ethno-pedagogical competence. The author describes the practical application of cognitive, operational-activity, communicative, motivational and reflective tasks.